Beethovens Auseinandersetzung um die Vormundschaft über seinen Neffen Karl aus historischer und soziologischer Perspektive - Kim, Jin-Ah (Die Musikforschung, 2020)
This article investigates from a historical and sociological perspective, Beethoven's struggle for the guardianship of his nephew, Karl, from November 1815 until September 1820. Its purpose is to illuminate Beethoven's knowledge and actions in the case of guardianship against the backdrop of contemporary historical and sociological conditions. In the early nineteenth century guardianship meant most certainly more than just the acceptance of legal custody of a minor; rather it was understood as an expression of the public recognition of talent, assets and social standing, as well as of character and honor. It furthermore functioned as an indicator of social status and position. Of great significance were also aspects of the position of legal guardian, the types of disputes with relatives, matters of family politics, the societal roles of fathers, issues of child-rearing, perceptions of status and rank, the traditional construction of gender difference and, lastly, norms of sexual behavior. The article reads Beethoven's letters and statements against the guardianship provisions of the Allgemeines Bürgerliches Gesetzbuch and contemporary legal practice, and argues that his struggle for Karl's guardianship was motivated by his ideas about social advancement through education as well as gendered norms of good parenthood.